'Nervous Wrecks' Me - Pearl - Elsie - Wingu - Howard - at Home Summer '31 - Fred Louis:::::: (1931)
Page of Fred Louis's scrapbook containing two images of family and friends. The image to the left displays two women wearing dresses standing in front of a house. The image to the right displays Fred, Pearl, Elsie, Wingu, and Howard (Toby) in front of their home.